2011
DOI: 10.1111/j.1524-475x.2011.00711.x
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and development of avotermin (recombinant human transforming growth factor beta 3): A new class of prophylactic therapeutic for the improvement of scarring

Abstract: Scarring in the skin following surgery or trauma may be associated with adverse aesthetic, functional, growth and psychological effects, such that both physicians and patients regard it as important to minimize the appearance of scars. The prophylactic improvement of cutaneous scar appearance represents a significant opportunity to improve the well-being of patients. Human recombinant transforming growth factor beta 3 (avotermin) is the first in a new class of therapeutic agents to address this medical need. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 33 publications
1
58
0
Order By: Relevance
“…When rhTGF-β3 was administered in adult wounds, scars were reduced. [23][24][25] (2) Extracellular matrix Hyaluronic acid is a major component of the fetal skin matrix, 26,27 and the increase in the ratio of hyaluronic acid in fetal wounds to that in the surrounding skin was higher than in adult wounds. [27][28][29] When procedures for decomposing hyaluronic acid in fetal wounds were car- Under a microscope, the flank skin of fetal mice was wounded in utero, and was harvested 72 h later (A).…”
Section: Molecular Differences (1) Growth Factorsmentioning
confidence: 99%
“…When rhTGF-β3 was administered in adult wounds, scars were reduced. [23][24][25] (2) Extracellular matrix Hyaluronic acid is a major component of the fetal skin matrix, 26,27 and the increase in the ratio of hyaluronic acid in fetal wounds to that in the surrounding skin was higher than in adult wounds. [27][28][29] When procedures for decomposing hyaluronic acid in fetal wounds were car- Under a microscope, the flank skin of fetal mice was wounded in utero, and was harvested 72 h later (A).…”
Section: Molecular Differences (1) Growth Factorsmentioning
confidence: 99%
“…Moreover, phase II clinical trials showed that intradermal injections of avotermin in scar revision surgery [94] and bilateral leg wounds [95] were well tolerated and resulted in significantly improved scar appearance compared to placebo. In addition, other phase II clinical trials demonstrated significant improvement in scar formation with avotermin treatment as well [96]. …”
Section: Regenerative Therapies For Skin Wound Managementmentioning
confidence: 99%
“…Recombinant human TGF-b3, Avotermin, has been demonstrated to be safe and numerous double-blind, placebo-controlled prospective trials has demonstrated statistically significant improvement in scar appearance at a range of doses and dose frequencies. 186 The key to any modulation of scar formation is the coordination of numerous cellular and molecular processes. Direct cytoplasmic coupling between cells mediated by gap junctions provides a direct line for the spread of biological information within tissues.…”
Section: Chemokines As Therapeutic Targetsmentioning
confidence: 99%